Navigating the Digital Frontier: Uncovering the Complexities of Online Learning in Higher Education - Meylina, Meylina (International Student Conference on Business, Education, Economics, Accounting, and Management (ISC-BEAM), 2024)
As higher education increasingly implements online learning, understanding its dynamics becomes very important. This research investigates the complex dynamics of online learning in Universitas Terbuka, focusing on the challenges and opportunities that exist. Using a mixed methods approach, this research explores the experiences, perceptions, and outcomes of 100 students engaged in online learning environments. Through surveys, interviews, and analysis of course materials, data was collected to reveal various aspects of online learning dynamics. These findings shed light on challenges such as technology barriers, student engagement, and assessment integrity, while identifying opportunities to improve flexibility, accessibility, and personalized learning experiences. Additionally, sociocultural factors, institutional support structures, and pedagogical strategies are examined for their impact on online learning dynamics. By synthesizing quantitative and qualitative insights, this research contributes to a deeper understanding of the complexity inherent in the dynamics of online learning and provides recommendations for optimizing its implementation in higher education contexts.